2008
DOI: 10.1126/science.1159806
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Type 17 Response to Viral Infection by CD8 + T Cells Lacking T-bet and Eomesodermin

Abstract: When intracellular pathogens invade mammalian hosts, naïve CD8+ T cells differentiate into cytotoxic killers, which lyse infected target cells and secrete cytokines that activate intracellular microbicides. We now show that CD8+ T cells deficient in the transcription factors T-bet and eomesodermin (Eomes) fail to differentiate into functional killers required for defense against lymphocytic choriomeningitis virus. Instead, virus-specific CD8+ T cells lacking both T-bet and Eomes differentiate into an IL-17-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
386
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 356 publications
(414 citation statements)
references
References 24 publications
25
386
2
1
Order By: Relevance
“…According to redundant functions between Eomes and T-bet, we did not observe differences in the accumulation of Eomes-deficient Th1 cells under inflammatory conditions or under steady state, despite the fact that the majority of Eomes + WT cells under those conditions were active producers of IFN-g. Therefore, we concluded that Eomes does not play an essential nonredundant role in Th1 responses in vivo, which is in line with previous reports (21,22).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…According to redundant functions between Eomes and T-bet, we did not observe differences in the accumulation of Eomes-deficient Th1 cells under inflammatory conditions or under steady state, despite the fact that the majority of Eomes + WT cells under those conditions were active producers of IFN-g. Therefore, we concluded that Eomes does not play an essential nonredundant role in Th1 responses in vivo, which is in line with previous reports (21,22).…”
Section: Discussionsupporting
confidence: 80%
“…Eomes restrains the age-dependent accumulation of CD4 + Foxp3 + T cells (21). In line with levels of Eomes + CD4 + T cells being very low in young animals, we did not observe any differences in the frequencies of IFN-g-or IL-17-producing CD4 + cells in 2-mo-old mice ( Fig.…”
Section: Eomes + Cd4 + T Cells Accumulate With Agesupporting
confidence: 65%
See 3 more Smart Citations